Molecular detection and phylogenetic characterization of Theileria equi in horses (Equus caballus) from a peri-urban area of Argentina - Sebastian, Patrick Stephan (2021)
To investigate the presence of Theileria equi in an endemic area of equine piroplasmosis 42 horses (Equus caballus) from Corrientes City, Argentina were sampled. Eighty-one percent (34 blood samples) of the analyzed horses were tested positive to the presence of piroplasmid 18S rDNA. All these samples could be identified as T. equi by amplifying the specific EMA-1 (merozoite antigen 1) gene of this species. Phylogenetic analysis of an obtained 18S rDNA complete sequence from one strain resulted in the identification of this sample as T. equi sensu stricto (genotype A). This study presents the first molecular detection and characterization of T. equi by the complete 18S rDNA sequence in Argentina. Based on these results further studies should be carried out to investigate the distribution and heterogeneity of presented genotypes of T. equi in Argentina, which is essential for the diagnosis, prevention and treatment of equine piroplasmosis.